ACCOUNTABILITY OF THE REGIONAL HOUSE OF REPRESENTATIVES (DPRK) IN DEVELOPMENT OF LOCAL LEGISLATION PROGRAM - Ansarullah Ansarullah; Eddy Purnama; efendi efendi (Kanun Jurnal Ilmu Hukum, 2022)
This study aims to analyse and final the ideal legal design of the accountability concept to legislative organ in particular Regional House of Representatives (DPRK). One of The authority of DPRK is stated in Article 24 paragraph (1) of Law Number 11 of 2006 on the Government of Aceh states that: "DPRK has the duty and authority to form district/city qanuns which are discussed with the regents/mayors for mutual approval". In that law, that has not been formulated specific forms of accountability of the legislative organ. In genuine, when the DPRK has not carried out its duties and functions effectively in the field of legislation, there has no legal consequences can be given. This research uses normative legal research with statutory and conceptual approach. The outcomes of this study indicate that, the concept of legislative accountability relates to two aspects, that is political and managerial accountability. This accountability should have electoral implications on the performance of the DPRK in carrying out its functions in the field of legislation. The implementation of legislative accountability on the performance of DPRK in the field of legislation has legal and political consequences.